Dielectric Properties of Upside-Down SrTiO3/Li2MoO4 Composites Fabricated at Room Temperature - Kuzmić, Nina; Škapin, Srečo Davor; Nelo, Mikko; Jantunen, Heli; Spreitzer, Matjaž (Frontiers in Materials, 2021)
In this paper, bulk ceramic upside – down lithium molybdate-strontium titanate (LMO-ST) composites fabricated at room temperature are described. Room-temperature fabrication (RTF) is a promising alternative to time- and energy-consuming high-temperature sintering of electroceramics, that encompasses mixing of the initial phases, moulding with a steel dye, pressing and drying, while in the latter two phases the action of densification takes place. The LMO-ST composites are based on a high ratio of filler ST, coupled with the corresponding LMO binder. A part of the binder is admixed to ceramic particles and additional part is added as a saturated aqueous solution, which crystallizes during pressing and drying, resulting to its deposition at the surface of filler particles. As a result, a sufficient binding with 76 to 84% relative density was achieved. The deeper insight in the method was given from various processing aspects, along with corresponding microstructural analysis. The particle size distribution, pressure, pressing time, ultrasound treatment, drying time, and processing conditions were optimized to obtain improved functional properties of LMO-ST composites. Results of this study with relative permittivity in the range of 65-78 and dielectric loss tangent values from 0.002-0.05 can attract considerable attention for the utilization of LMO-ST composites in the industry of electroceramics.